Changes of Periphyton Abundance and Biomass Driven by Factors Specific to Flooding Inflow in a River Inlet Area in Erhai Lake, China - Ren, Wenjing; Yao, Yiqian; Zhang, Zhonghai; Cao, Yu; Yuan, Changbo; Wang, Hao; Chou, Qing Chuan; Ni, Leyi; Zhang, Xiaolin; Cao, Te (Frontiers in Environmental Science, 2021)
Periphyton is an ecological essential in freshwater lakes and rivers. Its abundance and biomass are very dynamic in various habitats and subject to various factors, e.g. nutrient and light. Following flooding events, the transitional area adjacent to a river inlet and the shallow lake generates diverse habitats for periphyton with gradients in current velocity, suspended matters, nutrients and light, which would strongly shape the growth and community of periphyton. In this study, three sampling sites were established around a river inlet in Erhai Lake, China, and field survey was conducted in the sites from April to August (flooding seasons) in 2019 to investigate the abundance and biomass of periphyton and explore influential factors. The results showed that three study areas have different gradients of current velocity depended on the distance to the river inlet, thereby regulating the concentrations of nutrients and suspended matters, which strongly affected the periphyton community; to be specific, the biomass of periphyton was inhibited by the concentration of suspended matters and high concentrations of silicate mainly reduced the diversity of periphyton. Our results imply that the study on the driver factors of periphyton could help to understand its community assembly mechanism, and biomass and species composition of periphyton can provide some reference for trophic state of the lake.